If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + 29) + -12 = 80 Reorder the terms: 2(29 + m) + -12 = 80 (29 * 2 + m * 2) + -12 = 80 (58 + 2m) + -12 = 80 Reorder the terms: 58 + -12 + 2m = 80 Combine like terms: 58 + -12 = 46 46 + 2m = 80 Solving 46 + 2m = 80 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-46' to each side of the equation. 46 + -46 + 2m = 80 + -46 Combine like terms: 46 + -46 = 0 0 + 2m = 80 + -46 2m = 80 + -46 Combine like terms: 80 + -46 = 34 2m = 34 Divide each side by '2'. m = 17 Simplifying m = 17
| 7x-27+4x+12=180 | | x^2-x-66=6 | | 5x^3=125 | | x^4+x^2-2x-1=0 | | 42x^2+67x+21= | | 4y+ax=b+8y(x) | | x^3-x-2= | | -11*-24= | | -9x+9y=27 | | 15n+18=-6n+2 | | 2-2n=3(-n+2) | | 3m+8=3(4+m)-4 | | -48+(-13)= | | 6n+7-2n-14=4n+8 | | h(t)=-t-17 | | 3x^2-16x=64+y | | g(x)=5+0x | | 57+(-104)= | | x^2+x-48=3x | | 3n+6+n-8=2n-2+2n | | 3n+5(n-2)=3n+8(2-n) | | -43+81= | | 7(3-2n)-1=6-7n | | 52+(-7)= | | x^2-4x=-x+70 | | 5(3+x)-(8x+9)=-4 | | a(t)=12-4t | | -38+7= | | 10x+9=2x-7 | | 3x^4(1-x)=0 | | -3.2=-6.8 | | -16+-29= |